Covalent Inhibition in Drug Discovery. (26th March 2019) - Ghosh, Avick Kumar; Samanta, Indranil; Mondal, Anushree; Liu, Wenshe Ray
Abstract: Although covalent inhibitors have been used as therapeutics for more than a century, there has been general resistance in the pharmaceutical industry against their further development due to safety concerns. This inclination has recently been reverted after the development of a wide variety of covalent inhibitors to address human health conditions along with the US Food and Drug Administration (FDA) approval of several covalent therapeutics for use in humans. Along with this exciting resurrection of an old drug discovery concept, this review surveys enzymes that can be targeted by covalent inhibitors for the treatment of human diseases. We focus on protein kinases, RAS proteins, and a few other enzymes that have been studied extensively as targets for covalent inhibition, with the aim to address challenges in designing effective covalent drugs and to provide suggestions in the area that have yet to be explored. Abstract : For more than 100 years there has been a general reluctance toward covalent inhibitors, given safety concern. However, thanks to modern drug discovery approaches, the development of covalent inhibitors has been flourishing in the past decade. This review summarizes the history of covalent inhibitors and recent progress in their development.